Energy, entropy and cost analysis of a combined power and water system with cascade utilization of geothermal energy. (15th October 2018) - He, W.F.; Han, D.; Wen, T.
Highlights: A novel combined power and water system is proposed. Energetic, entropy and exergetic analysis of the combined system is achieved. Cost of the heat and mass transfer areas is calculated. Correlations between the system performance and the evaporation temperature are focused. Abstract: This paper proposed a novel combined system to achieve the cascade utilization of geothermal energy for joint power and water production. A regenerative organic Rankine cycle (ORC) is adopted as the top cycle, while a desalination system based on humidification dehumidification (HDH) principle with open-air architectures is applied to further utilize the geothermal energy. Based on the streams within the ORC and HDH units, the corresponding mathematical models with mass and energy conservation are established, and performance simulation according to thermodynamic laws is fulfilled. Furthermore, cost analysis of the combined system is also accomplished to reveal the correlations between the system economy and the involved parameters. The research results show that the actual peak values of net power, water production and gained-output-ratio (GOR) reach 42.68 kW, 236.81 kg h −1 and 1.42, and the total efficiency of the entire system is 31.19%. Based on the obtained thermodynamic performance, the bottom cost of the entire system is found as 4983.83 with a total heat and mass transfer areas of 104.27 m 2 at the balance condition of the humidifier. Furthermore, according to the influence analysis, an elevation of the evaporation temperature of the ORC, which is within the prescribed range, is beneficial to improve the thermodynamic performance and the relevant cost of the combined system.